Giant Nonfunctioning Parathyroid Cyst: A Case Report and Review of the Literature - Eoin F. Cleere; Mel Corbett; Anne-Marie Quinn; Thavakumar Subramaniam (Case Reports in Otolaryngology)
Parathyroid cysts are a rare clinical entity that may arise in the neck or mediastinum. They are more common in women and generally present in the fourth and fifth decades of life. Diagnosis of parathyroid cysts is challenging, and despite thorough radiological and cytological investigation, they are often mistaken for thyroid pathology. Definitive diagnosis is often only confirmed following complete surgical resection and histopathological analysis. We present the case of a woman who was referred to our outpatient clinic with a left-sided neck mass and associated compressive symptoms. Initial examination and investigation appeared consistent with a large thyroid nodule. Following surgical resection, the lesion was found to be a parathyroid cyst. Subsequently, we review the available literature on parathyroid cysts with particular emphasis on the diagnostic challenge they pose to clinicians.